2021
DOI: 10.1002/brb3.2052
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of emotions in healthy aging: age‐related differences in brain network connectivity

Abstract: Introduction Successful inhibition of distracting emotions is important for preserving well‐being and daily functioning. There is conflicting evidence regarding the impact of healthy aging on emotional inhibition, and possible age‐related alterations in the neuronal underpinnings of emotional interference processing are unexplored. Methods Thirty younger (mean age 26 years; 15 women) and 30 older (mean age 71 years; 13 women) healthy adults performed a face–word emotional Stroop task while undergoing functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 132 publications
(153 reference statements)
1
7
0
Order By: Relevance
“…Cognitive inhibition can be captured by paradigms including the Stroop, Flanker, and Simon and stimulus response compatibility (SRC) (Stahl et al, 2014;van Velzen et al, 2014;Almdahl et al, 2021). In the Stroop or Flanker tasks, participants are required to suppress interference due to stimulus competition or irrelevant information and need to resolve a conflicting representation arising from the cognitive level (Hung et al, 2018).…”
Section: Subcomponents Of Inhibitory Control and Its Neural Correlatesmentioning
confidence: 99%
“…Cognitive inhibition can be captured by paradigms including the Stroop, Flanker, and Simon and stimulus response compatibility (SRC) (Stahl et al, 2014;van Velzen et al, 2014;Almdahl et al, 2021). In the Stroop or Flanker tasks, participants are required to suppress interference due to stimulus competition or irrelevant information and need to resolve a conflicting representation arising from the cognitive level (Hung et al, 2018).…”
Section: Subcomponents Of Inhibitory Control and Its Neural Correlatesmentioning
confidence: 99%
“…Single-subject analysis of the fMRI data will be conducted using the general linear model (GLM) as implemented in SPM12. The conditions will be modeled as previously described for the eSTROOP ( 120 ), e-nBACK ( 124 ) and the ERT [similar to ( 123 )]. Image-derived movement estimates and surrogates of physiological artifacts (heartbeat, breathing) will be used as covariates and regressed out.…”
Section: Discussionmentioning
confidence: 99%
“…The fMRI implementation of the e-nBACK task will only consist of a 2-back and an additional 0-back condition as control organized in a mixed design [similar to ( 120 )]. The conditions will be presented in eight blocks (four per condition) of 12 stimuli, where the pictures are shown for 2 s with 0.5 s between.…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Existing studies focused on comparing older and young adults to explore the role of aging in influencing the process of emotion and response inhibition. Studies utilizing the emotional Stroop task, Stop-Signal task and Go/No-Go task found that healthy older adults with positive emotions had greater emotional response inhibition than younger adults ( Waring et al, 2019 ; Williams et al, 2020 ; Almdahl et al, 2021 ), and task-relevant happy information enhanced response inhibition in older adults. The older adults with pathologic cognitive impairment were not included in these studies.…”
Section: Introductionmentioning
confidence: 99%